DIVIDEND POLICY: ANALYSIS AND IMPLICATIONS FOR CORPORATE DECISIONS - Edy Purnomo; Muammar Khaddafi (CV. RADJA PUBLIKA, 2024)
The decision to distribute profits to shareholders is one of the key decisions taken by shareholders , and has a significant impact on company value and shareholder satisfaction. This article conducts an in-depth literature review to understand the concept of dividend policy and the various factors that influence it, such as the company's financial condition, investment needs, shareholder preferences, and market situation. The research method used is descriptive analysis carried out by collecting secondary data from various relevant sources. The research results provide valuable insights for companies in making better decisions regarding dividend policy, as well as offering practical guidance for policy makers and corporate managers in improving the transparency, effectiveness and adaptability of their dividend policies.